The Influence of Teacher Emotional Support and Mathematical Disposition on Students’ Academic Performance in Mathematics - Aila Sor Lanat; Emelyn Faelmoca; Jesalyn Manulat; Rheymark Vale (Journal of Social, Humanity, and Education, 2026)
Purpose: The study examined the influence of teacher emotional support and mathematical disposition on the academic performance of BSED Mathematics students Research Methodology: This study was conducted in Panabo City, Davao del Norte. The respondents were 120 first- and second-year BSED Mathematics students, utilizing a quantitative descriptive–correlational design. Data were collected through validated questionnaires on teacher emotional support and mathematical disposition and a researcher-made summative test in College and Advanced Algebra. Statistical analyses, including Pearson’s correlation and multiple regression, were performed using SPSS to examine the relationships among the variables. Results: Teacher emotional support and mathematical disposition were perceived as very evident, while students’ academic performance was high. No significant relationship was found between either teacher emotional support or mathematical disposition and academic performance, although a strong positive relationship existed between teacher emotional support and mathematical disposition. The regression results showed that neither variable significantly predicted academic performance. Conclusions: Despite the presence of teacher emotional support and positive mathematical disposition, these factors did not directly influence students’ academic performance in mathematics in this study Limitations: This study was confined to one institution and limited to selected emotional and attitudinal variables, restricting the generalizability of the findings. Contributions: This study offers insights into the role of emotional and attitudinal factors in mathematics education and underscores the need to examine other cognitive and instructional variables that may better explain students’ mathematics performance.